Best Practices from World Libraries Photo Gallery Project: Engaging Global Libraries. Issue 1 (2nd March 2020) - Liu, Grace; Mattson, Mark
Abstract: This article reports on the "2019 Best Practices from World Libraries" Photo Gallery Project initiated by the International Connections Committee (ICC) of the International Relations Round Table (IRRT) at the American Library Association (ALA). The project was inspired by a 2018 ALA-IRRT Emerging Leader's project, Toward Increasing Engagement of International New Professional Leaders in ALA Activities, which followed a survey study developed to explore IRRT's ability to engage its international members. The article shares the project planning process and the key actions taken to build a virtual and physical gallery for the 2019 ALA Annual Conference in Washington, DC, as well as highlights example programs from the project which demonstrate how libraries around the world are building stronger communities. Finally, the authors consider how the project may be improved upon and further developed in the future.